Enhancing e-learning effectiveness using an intelligent agent-supported personalized virtual learning environment: An empirical investigation - Xu, Dongming; Huang, Wayne W.; Wang, Huaiqing; Heales, Jon (Information & management, 2014)
Virtual learning environments (VLEs) developed under constructivism and embedded personalization learning functions have the potential to meet different requirements of different learners and thus increase e-Learning effectiveness. We formulated internal personalized learning mechanisms by implementing intelligent agents in a VLE under a constructivist learning model and further developed an e-learning effectiveness framework by integrating educational and IS theories. An empirical field experiment involving 228 university students was conducted. The findings suggested that personalized e-learning facilities enhance online learning effectiveness in terms of examination, satisfaction, and self-efficacy criteria.